Improvement of erinacine A productivity in Hericium erinaceus mycelia and its neuroprotective bioactivity against the glutamate-insulted apoptosis. (January 2016) - Chang, Chi-Huang; Chen, Yeh; Yew, Xin-Xiung; Chen, Hua-Xin; Kim, Jia-Xuan; Chang, Chun-Chao; Peng, Chiung-Chi; Peng, Robert Y.
Abstract: Hericium erinaceus (Bulliard: Fries) Persoon (HE), synonymously called Monkey Head mushroom or Yamabushitake, contains a huge amount of nutrients, in particular, the erinacines. This study was carried out with the aim to uncover whether erinacines can play a role as a neuroprotective adjuvant and what the related mechanism of action could be. A novel medium was developed to significantly enhance the productivity of biomass as well as erinacines to reach 16.8 g/L and 225 ± 54 mg/L, respectively. The ethanolic extract of HE (HEE) was tested on PC-12 cell line for its protective effect against the 20 mM glutamate-insult (GluI). The parameters affected were (control vs. GluI): glutathione (8.9 ± 0.8 vs. 2.5 ± 0.7 nmol/mg protein); glutathione peroxidase (11.6 ± 1.6 vs. 28.2 ± 3.2 mU/mg protein); glutathione reductase (9.2 ± 0.8 vs. 2.3 ± 0.4 mU/mg-protein); Ca 2+ -influx (115 ± 16 vs. 360 ± 23 nmol/L); reactive oxygen species (100 ± 3 vs. 140 ± 7%); superoxide dismutase (56.5 ± 6.3 vs. 23.2 ± 4.2 U/mg-protein); H2 O2 (8.2 ± 0.7 vs. 20.4 ± 3.5 nmol/mg-protein); and TBARs (MDA) (8.1 ± 0.3 vs. 13.3 ± 2.5 μmol/μg-protein) ( p  < 0.05). HEE effectively suppressed the ratio Bax/Bcl-2 and caspase-3, resulting in promising inhibition on PC-12 cell apoptosis induced by Glu-insult. Conclusively, the novel medium enhances both the productivity of biomass and erinacine A and its extract can effectively prevent PC-12 apoptosis via the ROS-caspase dependent pathway. Highlights: Productivity of erinacines was improved in Hericium erinaceus (HE). Promising neuroprotective effect was found against glutamate insult (GluI). Parameters for alleviation associated with neuroprotection included glutathione. Glutamate-insulted apoptosis of PC-12 cells was secured.